Toll-like Receptor 2 is Involved in Calcium Influx and Acrosome Reaction to Facilitate Sperm Penetration to Oocytes During in vitro Fertilization in Cattle - Ma, Dongxue; Marey, Mohamed Ali; Shimada, Masayuki; Miyamoto, Akio (Frontiers in Cell and Developmental Biology, 2022)
Cumulus cells of ovulated cumulus-oocyte complexes (COCs) express Toll‐like receptor 2 (TLR2), pathogen recognition receptors, to recognize and react to sperm signals during fertilization. Sperm also express TLR2, but its contribution to the sperm-oocytes crosstalk is still unclear. Here, we adapted the in vitro fertilization (IVF) model to characterize the potential relevance of sperm TLR2 in sperm-oocytes interactions during fertilization in bovine. The IVF results showed that the ligation of sperm TLR2 with its specific antagonist/agonist resulted in down/up-regulation of the cleavage and blastocyst rates either in COCs or cumulus-free oocytes, but not in zona pellucida (ZP)-free oocytes. The computer-assisted sperm analysis (CASA) system revealed that sperm motility parameters were not affected in TLR2 antagonist/agonist-treated sperm. However, fluorescence imaging of sperm-ZP interactions revealed that the blockage or activation of the TLR2 system in sperm reduced or enhanced both binding and penetration abilities of sperm to ZP compared to control, respectively. Flow cytometrical analysis of acrosome reaction (AR) demonstrated that the TLR2 system adjusted the occurrence of AR in ZP-attached sperm, suggesting that sperm TLR2 plays physiological impacts on the sperm-oocyte crosstalk via regulating ZP-triggered AR in sperm. Given that calcium (Ca2+) influx is a pre-requisite step for the induction of AR, we investigated the impact of the TLR2 system on the ionophore A23187-induced Ca2+ influx into sperm. Notably, the exposure of sperm to TLR2 antagonist/agonist reduced/increased the intracellular Ca2+ level in sperm. Together, these findings shed new light that the TLR2 system is involved in sperm AR induction which enables sperm to penetrate and fertilize oocytes during the fertilization, at least in vitro, in cows. This suggests that sperm possibly developed a quite flexible sensing mechanism simultaneously against pathogens as well as COCs toward fertilization with the same TLR2 of the innate immune system.